Coupling mechanisms coordinating mRNA translation with stages of the mRNA lifecycle - Valeria Famà; Lucia Coscujuela Tarrero; Roberto Albanese; Lorenzo Calviello; Stefano Biffo; Mattia Pelizzola; Mattia Furlan (RNA Biology)
Gene expression involves a series of consequential processes, beginning with mRNA synthesis and culminating in translation. Traditionally studied as a linear sequence of events, recent findings challenge this perspective, revealing coupling mechanisms that coordinate key steps of gene expression, even when spatially and temporally distant. In this review, we focus on translation, the final stage of gene expression, and examine its coupling with key stages of mRNA metabolism: synthesis, processing, export, and decay. For each of these processes, we provide an overview of known instances of coupling with translation. Furthermore, we discuss the role of high-throughput technologies in uncovering these intricate interactions on a genome-wide scale. Finally, we highlight key challenges and propose future directions to advance our understanding of how coupling mechanisms orchestrate robust and adaptable gene expression programs.